2006
DOI: 10.1051/0004-6361:20066319
|View full text |Cite
|
Sign up to set email alerts
|

Properties of planets in binary systems

Abstract: Aims. The statistical properties of planets in binaries were investigated. Any difference to planets orbiting single stars can shed light on the formation and evolution of planetary systems. As planets were found around components of binaries with very different separation and mass ratio, it is particularly important to study the characteristics of planets as a function of the effective gravitational influence of the companion. Methods. A compilation of planets in binary systems was made; a search for companio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
249
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(263 citation statements)
references
References 83 publications
13
249
0
1
Order By: Relevance
“…5), where more massive planets have on average higher mean eccentricities. Overall, we corroborate the conclusions of Desidera & Barbieri (2007) that wide companions seem to have less influence on the properties of planets than closer systems.…”
Section: Dynamical Properties Planet-host Starssupporting
confidence: 89%
See 3 more Smart Citations
“…5), where more massive planets have on average higher mean eccentricities. Overall, we corroborate the conclusions of Desidera & Barbieri (2007) that wide companions seem to have less influence on the properties of planets than closer systems.…”
Section: Dynamical Properties Planet-host Starssupporting
confidence: 89%
“…1, where we assumed the planet-host star distance to determine a possible absolute J-band magnitude. We note that the companion to HD 213240 was already published by Mugrauer et al (2005b) and that Desidera & Barbieri (2007) already reported a wide companion to HD 109749 but at a closer separation.…”
Section: Search Criteriasupporting
confidence: 64%
See 2 more Smart Citations
“…However, in the mass-period and eccentricity-period diagrams, HD 16760b is located in a region not populated much by planets in binary systems. The discovery of this long-period, loweccentricity planet thus adds to the growing evidence that, in contrast to short-period planets, long-period ( > ∼ 100 days) planets residing in binaries possess the same statistical properties as their counterparts orbiting single stars (Eggenberger et al 2004;Mugrauer et al 2005;Desidera et al 2007).…”
Section: Discussionmentioning
confidence: 76%